If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 142 = 7 + 3(-7x + 3) Reorder the terms: 142 = 7 + 3(3 + -7x) 142 = 7 + (3 * 3 + -7x * 3) 142 = 7 + (9 + -21x) Combine like terms: 7 + 9 = 16 142 = 16 + -21x Solving 142 = 16 + -21x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '21x' to each side of the equation. 142 + 21x = 16 + -21x + 21x Combine like terms: -21x + 21x = 0 142 + 21x = 16 + 0 142 + 21x = 16 Add '-142' to each side of the equation. 142 + -142 + 21x = 16 + -142 Combine like terms: 142 + -142 = 0 0 + 21x = 16 + -142 21x = 16 + -142 Combine like terms: 16 + -142 = -126 21x = -126 Divide each side by '21'. x = -6 Simplifying x = -6
| g-1.6=2.8 | | .8*X=24 | | 14+12v=-16+9 | | 20-43=3(x-1)-5 | | 0=6x+13 | | j-3.79=14.21 | | 21y-1=4x+23+9x-38 | | y=6(0)+13 | | 80*X=24 | | x+2x+(x+3)=75 | | 11b-12=-10 | | f+6=8 | | 6(5)-1=5(5-1)-3(7-2(1)) | | 5=q+2 | | 9(0)-7y=14 | | 10x-3=20+15 | | -8n+5(4n+8)=100 | | 2x-5x+3x-25+5x+45=180 | | -3p-6(5-2p)=4(p-2)-47 | | .1x+10=.35x | | -2=w^7 | | 5x+7=2.5(2x+2.8) | | 9x-7(0)=14 | | 6(5)=5(5-1)-3(7-2(1)) | | f-8=11 | | 8sin^2(30)=y | | 5n^2-22n+24=0 | | 11(x-6)=-5-6 | | 49m^2+12=56m | | -4(4k+6)=-3k+2 | | 9=X*36 | | 6x+3x=189 |